Modulation of waveguide behaviour of an ICT 2H-benzo[d][1,2,3]triazole derivative with graphene - Torres, Iván; Romero-Nieto, Carlos; Rominger, Frank (Organic electronics, 2019)
Needle-like supramolecular structures prepared by the organized aggregation of a 2H-benzo[d][1,2,3]triazole derivative with few-layer graphene using the slow diffusion technique are described. The as-prepared aggregate shows, by using scanning electron microscopy (SEM), the formation of needles with graphene attached on the surface, which was corroborated by Raman spectroscopy and optical microscopy. The graphene-modified aggregate acts as a selective optical waveguide for green light, in contrast to the pristine aggregate which emits green and red light. These new materials may be of crucial importance for the development of high-performance optoelectronic devices.
Gesehen am 28.03.2019